In vivo and in vitro antidiabetic effects of Clerodendrum longisepalum - Supat Phaopongthai; Jirapast Sichaem; Jatuporn Phaopongthai (Songklanakarin Journal of Science and Technology (SJST), 2017)
This study aimed to investigate the antidiabetic properties of Clerodendrum longisepalum. This primary screening study focused on blood glucose levels and hematological values in diabetic rats treated with the leaf extract from C. longisepalum (CL). Results showed that the CL extract can lower the blood glucose level of the experimental animals from the diabetic state. In relation to this, the extract caused the hematological value in diabetic rats to drop close to normal controls. However, the in vitro α-glucosidase assay-guided isolation revealed that the stem extract of C. longisepalum has a possible connection with the inhibition of intestinal α-glucosidase. Three triterpenoids (1-3), one glycerol derivative (4) as well as six phenylpropanoid glycosides (5-10) were isolated. Compound 10 possessed good anti-α-glucosidase activity (maltase). A kinetic investigation of 10 indicated that it retarded maltase function in a noncompetitive manner. Moreover, compounds 6, 9 and 10 also showed good antioxidant activity (DPPH).